Representing a Model for Implementing International Financial Reporting Standards in Iran //Representación de un modelo para implementar las Normas Internacionales de Información Financiera en Irán - Dargahi, Esmaeil; Tahriri, Arash (Revista de la Universidad del Zulia, 2020)
Abstract International Financial Reporting Standards (IFRS) are global, identical, high-quality and comprehensive standards for financial reporting that have been developed by the International Accounting Standards Board (IASB). The objective of the current study is to represent a model for the implementation of the International Financial Reporting Standards in Iran. This study is an applied research and can be considered a qualitative research. A survey is applied in this regard. The statistical population of the study consisted of members of the accounting faculty of universities, financial managers, and boards of directors of companies listed on the Tehran Stock Exchange and the Iran Fara Stock Exchange. In this study, the snowball sampling method was used. In this research, 15 experts were initially selected as the initial research sample, then 25 people were added to the initial research volume, and 40 people were selected as the final sample. Based on the results of the interpretive structural model, cultural factors are the prerequisites for all factors that affect the adoption and dissemination of International Financial Reporting Standards (IFRS), and the cost and benefits of applying IFRS have the same greater impact on the adoption and dissemination of these standards. Resumen Las Normas Internacionales de Información Financiera (NIIF) son normas globales, idénticas, de alta calidad y comprensibles para la información financiera que han sido desarrolladas por el Consejo de Normas Internacionales de Contabilidad (IASB). El objetivo del estudio actual es representar un modelo para la implementación de las Normas Internacionales de Información Financiera en Irán. Este estudio es una investigación aplicada y puede considerarse una investigación cualitativa. Se aplica al respecto una encuesta. La población estadística del estudio consistió en miembros de la facultad de contabilidad de las universidades, gerentes financieros y juntas directivas de empresas que cotizan en la Bolsa de Valores de Teherán y la Bolsa de Irán Fara. En este estudio, se utilizó el método de muestreo de bola de nieve. En esta investigación, en un principio se seleccionaron 15 expertos como muestra inicial de la investigación y luego se agregaron 25 personas al volumen inicial de la investigación, y se seleccionaron 40 personas como muestra final. Con base en los resultados del modelo estructural interpretativo, los factores culturales son los requisitos previos para todos los factores que afectan la adopción y difusión de las Normas Internacionales de Información Financiera (NIIF), y el costo y los beneficios de aplicar las NIIF tienen el mayor impacto en la adopción y difusión de estos estándares.